Regional disparity in homeownership, investment choice, and intra-household bargaining: evidence from Chinese household surveys - Zhang, Fan (2018)
This thesis contains three studies that provide theoretical and empirical evidence on household decisions in housing and investment portfolios in China, using 2010-2014 data from the China Family Panel Studies (CFPS).